Characteristics, Properties and Analytical Methods of Paclitaxel: A Review - Alves, Renata Carolina [UNESP]; Fernandes, Richard Perosa [UNESP]; Eloy, Josimar O. [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2018)
Paclitaxel is a diterpenoid pseudoalkaloid, isolated from Taxus brevifolia, and is largely used as an antitumoral drug. The formulation of paclitaxel known as Taxol® employs a mixture of Cremophor EL and dehydrated ethanol, due the low drug water solubility. However, Taxol® causes some unwanted side effects due to the presence of Cremophor EL and ethanol in the formulation. Based on this, there is a need for the development of drug delivery systems to enhance the solubility, permeability and stability of paclitaxel and to promote a controlled and targeted delivery for better therapeutic effect and reduced side effects. In addition, the drug has been qualitatively and quantitatively analyzed in different delivery systems. In this context, several approaches were reported focusing on the optimization of analytical methods and development of new ones, considering the need of a fast, simple, with enough sensibility and selectivity assay, which can be a problem in some analysis. This review presents a summary of methods used in quantification of paclitaxel in different matrices, such as plasma, urine, plant extract, cells and delivery systems.
Keywords: Analytical methods; drug delivery systems; paclitaxel; physicochemical properties